Sireny, ili stranstvie po strane smertiSirene ali potovanje po deželi smrti - Yevzlin, Mikhail (Studia mythologica Slavica, 2015)
<span style="line-height: 115%; font-family: 'Calibri','sans-serif'; font-size: 11pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: 'Times New Roman'; mso-bidi-theme-font: minor-bidi; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">It is the aim of this paper to reinterpret Old Greek »singing« deities, the sirens, described mainly in Homer’s Odyssey, but also in later sources from antiquity. The author first analyzes cosmological parameters of Homer’s work, suggests an innovative view of the structure and organization of the world, and emphasizes the chtonic character of the cosmos through which Odysseus travels. The hero’s journey to Ithaca, during which he encounters different elements of the chtonic world, thus resembles a journey to the land of the dead. The author especially emphasizes the semiotic explanation of the meeting of Odysseus with the sirens. The paper also contains a typological comparison of sirens with other chtonic creatures from the same mythological tradition (Harpies, Scylla and Carybde), etc.), and analyzes other motifs from the Greek epic tradition within the general mythological framework of »chtonism«.